TRANSFORMING POLICY APPROACHES: EMPOWERING GENDER MAINSTREAMING IN ENVIRONMENTAL POLICIES OF SOUTH KALIMANTAN - Lena Hanifah (Faculty of Law, Universitas Pekalongan, 2022)
This socio-legal study highlights the pressing need to incorporate women's voices and experiences in Indonesia's natural resource management policies, particularly in South Kalimantan. This research employs an interdisciplinary approach, utilising qualitative and normative methods. The study investigates how to integrate gender perspectives into policy environments that are often gender-neutral and why it is crucial to include these perspectives in policy-making, especially in the context of South Kalimantan. The finding reveals that women's exclusion from the policy-making process is attributed to the policymakers' belief that the field should be gender-neutral. However, this approach has had adverse effects, resulting in increased gender discrimination instead of mitigating it.